Training on Making Batik Jumput Tei Dye PKK and UMKM Pagertanjung Village, Ploso District - Faisol Hamid; Aditya Harja Nenggar; Yully Wahyu Sulistyo; Joan Rhobi Andrianto (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
UMKM can improve the community's economy. UMKM can create community creativity and create new markets. The problem found in Pagertanjung Village, Ploso District is that there are still few UMKM. The survey results stated that some of them have interest but still have not found the idea and motivation to open a business. There are also those who have no interest in opening a business because their profession is a farmer. Therefore, the solution we provide is twofold. First, providing training by processing natural resources that are easily found in Pagertanjung Village, Ploso, namely batik jumput tie dye. Training on tie dye batik processing is given training and making tie dye batik. The product of this training is called Batik jumput tie dye. The benefits of this training are so that business actors can make and market their products more widely. The public can also add insight into the manufacture of jumput batik with various motifs, making tie dye jumput batik labels, and good marketing. It is hoped that this training can provide ideas and motivation for the community to open a business so that it can improve the economy of Pagertanjung Village, Ploso.